2020
DOI: 10.3390/ijms21176345
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Bacteriophage vB_EfaS-271 Infecting Enterococcus faecalis

Abstract: A newly isolated bacteriophage infecting Enterococcus faecalis strains has been characterized, including determination of its molecular features. This phage, named vB_EfaS-271, has been classified as a Siphoviridae member, according to electron microscopy characterization of the virions, composed of a 50 nm-diameter head and a long, flexible, noncontractable tail (219 × 12.5 nm). Analysis of the whole dsDNA genome of this phage showed that it consists of 40,197 bp and functional modules containing genes coding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 99 publications
1
20
0
Order By: Relevance
“…Since development of phage therapy against E. faecalis appears to be important to establish effective treatments of infections by antibiotic-resistant strains of this bacterium [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ], and biofilm formation on catheters is one of the most difficult medical challenges caused by this species [ 13 ], we aimed to test efficiency of recently isolated and described bacteriophage vB_EfaS-271 [ 26 ] in killing E. faecalis cells included in biofilms formed on Foley silicone catheters. We found that vB_EfaS-271 is able to efficiently reduce number of viable bacterial cells under such conditions ( Figure 1 ), providing evidence for its possible use in medical practice to either prevent colonization of catheters by E. faecalis or eradication of this bacterium from already formed biofilms in these medical devices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since development of phage therapy against E. faecalis appears to be important to establish effective treatments of infections by antibiotic-resistant strains of this bacterium [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ], and biofilm formation on catheters is one of the most difficult medical challenges caused by this species [ 13 ], we aimed to test efficiency of recently isolated and described bacteriophage vB_EfaS-271 [ 26 ] in killing E. faecalis cells included in biofilms formed on Foley silicone catheters. We found that vB_EfaS-271 is able to efficiently reduce number of viable bacterial cells under such conditions ( Figure 1 ), providing evidence for its possible use in medical practice to either prevent colonization of catheters by E. faecalis or eradication of this bacterium from already formed biofilms in these medical devices.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriophage vB_EfaS-271 was isolated from urban sewage (Gdansk Wastewater Treatment Plant, Poland) and deposited in the collection of phage strains of the Department of Molecular Biology of the University of Gdansk [ 26 , 28 ]. To obtain purified vB_EfaS-271 particles, E. faecalis 271 host was cultivated in the liquid TSB medium at 37 °C to an OD 600 of 0.3.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mass spectrometry data is crucial as it enables a discrimination between false positive (FP; predicted but not present by mass spectrometry of the virion) and true positive (TP; predicted and found present by mass spectrometry of the virion). Phage vB_EfaS_271 infects Enterococcus faecalis (26), phage vB_PatM_CB7 infects Pectobacterium atrosepticum (27), and phage vB_Eco4M-7 infects enteropathogenic Escherichia coli (28). STEP 3 was benchmarked against equivalent predictors: PVPred, PVP-SVM, PVPred-SCM and Pred-BVP-Unb (Fig.…”
Section: Resultsmentioning
confidence: 99%